An electricity consumption tracking meter - Ranjit Singh, Sarban Singh; Siva Kumar, Subramaniam; Siti Aisyah, Anas (2014)
The present invention relates to an electricity consumption tracking meter comprising: a 5v voltage supply circuit; a main controller circuit; an energy tracking circuit including a current transformer circuit; and a display unit circuit to display meter reading; characterized in that the energy tracking circuit and the main controller circuit calculate the consumption of the electricity and its rate straight away in real time and display the reading on the display unit of the display unit circuit besides saving the data in the microcontroller. The above provision is advantageous as the ordinary electric meter is just used to measure the consumed electricity without displaying the price for the consumer to watch. However, the present invention capable to measure, calculates, saves and instantly display the utilized electricity based on real time measurement.